(untitled) (Journal of Maternal and Child Health, 2019)
Background: Anemia in pregnant women remains a health priority to be addressed immediately. Anemia in pregnant women may increase the risk of maternal mortality, abortion, perinatal death, low birth weight, and postpartum bleeding. This study aimed to examine the contextual effect of posyandu on adherence to iron tablet consumption among pregnant women in Blitar, East Java. Subjects and Method: This was a cross-sectional study conducted in Blitar, East Java, in November 2018. The dependent variable was adherence of iron tablet consumption. The independent variables were education, intention, attitude, perceived behavior control, family income, subjective norm, husband support, and posyandu. The data were collected by questionnaire and analyzed by a multilevel linear regression run on Stata 13. Results: Iron tablet consumption increased with high education (b= 0.85; 95% CI= 0.05 to 1.66; p= 0.038), strong intention (b= 0.40; 95% CI= 0.02 to 0.77; p= 0.037), multiparity (b= 0.89; 95% CI= 0.15 to 1.62; p= 0.018), positive attitude (b= 0.29; 95% CI= 0.15 to 0.42; p<0.001), perceived behavior control (b= 0.33; 95% CI= 0.17 to 0.48; p<0.001), high family income (b= 0.05; 95% CI= 0.01 to 0.10; p= 0.018), iron tablet availability (b= 1.62; 95% CI= 0.84 to 2.40; p<0.001),strong husband support (b= 0.22; 95% CI= 0.04 to 0.40; p= 0.019), and subjective norm (b= 0.27; 95% CI= 0.03 to 0.52; p= 0.027). Iron tablet consumption decreased with side effect (b= -1.22; 95% CI= -2.12 to -0.33; p= 0.007). Posyandu had contextual effect in adherence to iron tablet consumption with ICC= 12.58%. Conclusion: Iron tablet consumption increases with high education, strong intention, multiparity, positive attitude, perceived behavior control, high family income, iron tablet availability, strong husband support, and subjective norm. Iron tablet consumption decreases with the side effect. Posyandu has contextual effect in adherence to iron tablet consumption. Keywords: Fe tablet consumption, posyandu, multilevel analysis Correspondence: